Certainty assessment in informal language - Mamani Sanchéz, Liliana (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2015)
This research studied linguistic hedges in informal language style. Hedges are expressions that show a weakened commitment of speakers with respect to what they are saying. This modification in their commitment is made for various reasons; to show their personal stance, to show their state of knowledge or to show politeness as a deference to potential readers. At the same time, their motivations stem from their caring about how they are perceived and from their wish to be more precise in their evaluations.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin